Statistical appraisal of economic design strategies of LV distribution networks - Gan, Chin Kim; Pierluigi, Mancarella; Pudjianto, Danny; Strbac, Goran (Elsevier B.V., 2011)
This paper presents a statistical approach for assessing general LV distribution network design strategies based on a large set of realistic test networks and optimal economic circuit design. The test networks are generated using a fractal-based algorithm that allows creation of generic networks with various topological features (e.g., typical of rural/urban/mixed areas) and characterised by different numbers of substations, numbers of customers, load densities, and so forth. In comparison to standards derived from a traditional approach, that is, case studies on a small number of specific real or test networks, the proposed approach facilitates the derivation of more robust conclusions on optimal network design policies and can thus be used as a valuable tool for decision support. The methodology is exemplified through numerical applications for both urban and rural areas.